Nano-optical photoresponse mapping of superconducting nanowires with enhanced near infrared absorption. (2nd November 2018) - Erotokritou, Kleanthis; Heath, Robert M; Taylor, Gregor G; Tian, Cheng; Banerjee, Archan; Casaburi, Alessandro; Natarajan, Chandra M; Miki, Shigehito; Terai, Hirotaka; Hadfield, Robert H
Abstract: Superconducting nanowire single-photon detectors (SNSPDs) play an important role in emerging optical quantum technologies. We report on advanced nanometric characterization of a high efficiency near infrared SNSPD design based on a low roughness tantalum pentoxide (Ta2 O5 )/silicon dioxide (SiO2 ) distributed Bragg reflector (DBR) cavity structure. We have performed high resolution transmission electron microscopy analysis to verify the smoothness of the DBR. Optical reflectance measurements show excellent correspondence with DBR simulations. We have carried out precision nano-optical photoresponse mapping studies at 940 nm wavelength at T  = 3.5 K, indicating excellent large area device uniformity (peak efficiency 55% at 100 Hz dark count rate (DCR)) with a full width half maximum timing jitter of 60 ps. With manual fibre coupling with single mode fibre, we achieve a system detection efficiency (SDE) of 57.5% at 940 nm wavelength (100 Hz DCR) at T  = 2.3 K and a low polarization dependence of 1.20 ± 0.03. For coupling with multimode fibre, we achieve SDE of 90% at 940 nm (200 Hz DCR) at T  = 2.3 K. These SNSPD devices are promising candidates for use in quantum dot photoluminescence studies and optical quantum technology applications.